How do young soccer players train? A 5-year analysis of weekly microcycle training load characteristics in an elite youth academy - Connolly, D. R.; Stolp, S.; Gualtieri, A.; Franceschi, A.; Ferrari Bravo, D.; Rampinini, E.; Coutts, A. J. (International Journal of Sports Science & Coaching, 2025)
This study aimed to describe the distribution of training load (session rating of perceived exertion (sRPE), duration, and sRPE-training load) across weekly microcycles of an elite youth academy and assess the differences between four different age groups (U15-U16-U17-U19). Training load variables were recorded during in-season training weeks over 5 competitive seasons (from 2014-15 to 2018-19, evaluating new squads for each age group each season) for a total of 456 player observations. Mixed models assessed the variability of the three load variables across the different training days of a weekly microcycle and between the four different age groups. Estimated marginal means, 95% confidence intervals (CI), and effect sizes (d) were calculated for each training day of the microcycle. The main findings were significant differences in the training load variables three and four days before the next Match Day (i.e., MD-3 and MD-4, respectively), with U15 recording lower sRPE (-2.0 AU, d = 0.43-0.72) and U19 a lower duration (-35 min, d < -1.10). All age groups reduced sRPE-training load in the two days before a match, mainly due to a decrease in training duration (-160 AU & -17 min respectively). Match days provided the highest training loads within the weekly microcycle, with moderate-to-large differences between the four age groups (d = 0.77, 1.16 and 1.38 for U15 vs U16-U17-U19 respectively). The low variability in sRPE values in the three central sessions of a weekly microcycle indicates that training duration is an important factor to control when aiming to manipulate within-week training loads in elite youth soccer players.